Outsiderzy poszukujący sensu życia (Mury Hebronu, Biały kruk, Przez rzekę, Dziewięć, Taksim) - Kwolek, Justyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
In the adumbration titled “Outsiders looking for the meaning of life”, the author shall present several groups of selected characters portrayed in the prose by Andrzej Stasiuk. Among the discussed groups one finds prisoners described in Mury Hebronu, wanderers accounted for in Biały Kruk and Taksim, femme fatales portrayed in the storybook titled Przez rzekę, as well as tragic heroes illustrated in the novel Dziewięć. All these characters might be said to stay in some kind of relationship because they share the overwhelming feeling of alienation – either by choice or due to the rejection from the society – and they all struggle to find any deep meaning in human life in the senseless surrounding world, but – unfortunately – the fail. The feeling of loneliness, alienation and the existential fear are the features which might be used to portray all the characters of the aforementioned prose.
Keywords: outsider; emptiness; roam; alienation; quest